PERANCANGAN SISTEM INFORMASI UJIAN ONLINE BERBASIS WEB PADA MTS AL-JAUHAROTUNNAQIYYAH CIBERKO DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Bafaqih, Ali; Auliana, Sigit; Purnama, Eris Dwi (Cattleya Darmaya Fortuna, 2025)
Madrasah Tsanawiyah Al-Jauharotunnaqiyyah Ciberko is a school in the city of Cilegon. At this school, exams are done by hand. Teachers print out test papers with multiple choice questions, and students answer them all together within a set time. Using this exam method often causes problems, like taking a long time to prepare the questions and making mistakes when grading. To fix these issues, a computer-based system is needed. The concept is to create a web-based online exam information system. The author built an online system for exam information using the waterfall approach. For system design, they used UML. The programming language chosen was PHP, which works with MYSQL to manage the database. They also used the Codeigniter framework because it is flexible and makes web development easier. The main goal of this study was to design a web-based system that helps teachers create questions more easily, send questions to students, let students complete exams, and quickly summarize exam results. This system made the online exam process more efficient. It also helped students work on their exams smoothly and allowed teachers to enter questions and scores accurately.